Georgia positions itself on China's new Silk Road: Relations between Tbilisi and Beijing in the light of the Belt-and-Road Initiative - Franziska Smolnik (Stiftung Wissenschaft und Politik (SWP), 2018)
China's importance and presence in Georgia are growing. The Belt and Road Initiative, Beijing's vision of a new Silk Road, has met with active approval here - in contrast to a number of West European capitals, where the project is instead increasingly viewed with reservations or scepticism. The government in Tbilisi is carefully positioning Georgia as an essential part of the south Eurasian corridor. In order to profit from future trade flow between China and Europe, it has implemented a series of measures. In 2017, it became the first country in Eurasia to conclude a free-trade agreement with China. Large infrastructure projects are being carried out to facilitate transit. Georgia is also using formats such as the Tbilisi Belt & Road Forum to promote its location. However, whether the new Silk Road will be a purely win-win situation for the country, still remains to be seen.
Keywords: 320